PENGARUH PREFERENSI KLIEN, PENGALAMAN AUDITOR, DAN INDEPENDENSI AUDITOR TERHADAP AUDIT JUDGEMENT PADA KANTOR AKUNTAN PUBLIK DI KOTA PEKANBARU - Zulhelmy; Luthfi, At Tariq (Journal Of Islamic Finance And Accounting Research, 2024)
The purpose of this study is to analyze the effect of client preferences, auditor experience, and auditor independence on audit judgment at a public accounting firm in Pekanbaru City. The population in this study are all Public Accounting Firms located in Pekanbaru City which are registered in the Directory of the Indonesian Institute of Certified Public Accountants (IAPI). The type of research conducted is quantitative research. Data was collected by distributing questionnaires which were filled out directly by all auditors working at the Public Accounting Firm in Pekanbaru City. Then the data obtained were analyzed using multiple linear regression analysis techniques, descriptive statistical test, classical assumption test, coefficient of determination test, t test, and f test. The results showed that simultaneously client preference, auditor experience, and Auditor Independence had a significant effect on audit judgment at the Public Accounting Firm in Pekanbaru City. Partially, client preference has a significant effect on Audit Judgment, Auditor Experience has a significant effect on Audit Judgment, and Auditor Independence has a significant effect on Audit Judgment at Public Accounting Firms in Pekanbaru City.